Business Reputation of a Social Entrepreneurship Entity: Conceptual Basis of the Concept - T. V. Varkulevich; V. A. Beloglazova (Управленческие науки, 2025)
The article examines the conceptual apparatus of business reputation and analyzes its key features in the field of social entrepreneurship. Particular attention is paid to the role of business reputation in strengthening ties between social entrepreneurship entities and society, as well as its importance in drawing attention to social problems. The purpose of the study was to form the author’s definition of business reputation in the context of the theory of social change, facilitating the implementation of new approaches to its assessment and management. The research methods were the analysis and systematization of scientific literature on business reputation and social entrepreneurship; content analysis of publications devoted to social change, as well as data visualization to present the evolution of theories and approaches. The authors of the article describe tools that allow social entrepreneurs to effectively use reputation to promote their initiatives and achieve goals. Despite the high interest in this topic, the scientific literature does not offer a sufficient number of works that consider the evolution of approaches to the assessment and management of business reputation in the context of social entrepreneurship, as well as its role in social change. The results of the study may be useful both for managers of organizations whose activities are related to the social sphere, to raise awareness of the importance of business reputation and its role in achieving social change, and for researchers studying business reputation issues, as materials for further professional research.